Review paperSupplementation with long chain polyunsaturated fatty acids in treatment of atopic dermatitis in children - Kaczmarski, Maciej; Cudowska, Beata; Sawicka-Żukowska, Małgorzata; Bobrus-Chociej, Anna (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2013)
Some recent studies indicate that unsaturated fatty acids, components of cellular membranes and precursors of immunomodulators, play a significant role in the pathogenesis of some symptoms of atopic dermatitis. Since they cannot be synthesized by the human body, they must be provided with nutrition as the so called exogenous fatty acids: linoleic (a precursor of arachidonic acid) and α-linolenic acid (a precursor of eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA)). Their deficiency facilitates the development of some disorders, e.g. of the cardiovascular system or of the nervous system, or becomes the cause of intensification of ailments in their course e.g. pruritus and dryness in atopic dermatitis. Though clinical examinations to date confirm the efficacy of fatty acid supplementation in treatment of atopic dermatitis, their results are not explicit.